Accumulation of Ade+ reversions in isoauxotrophic stains of Saccharomyces cerevisiae allelic in RAD6 during adenine starvation - Storchová, Z; Gil, A P; Janderová, B; Vlasák, J; Vondrejs, V (Folia microbiologica, 1997)
A comparative method based on an analysis of accumulation of starvation-induced Ade+ reversions and cell death during adenine starvation was developed and exploited for estimating the role of RAD6 in the starvation-induced reversions. It was shown that inactivation of RAD6 function in Saccharomyces cerevisiae markedly enhances the accumulation of Ade+ reversions, and therefore it is likely that this gene is taking part in maintaining the low level of starvation-induced mutations in yeast cells.
Keywords: Saccharomyces cerevisiae - proteiny; Saccharomyces cerevisiae; alely; Adenine; DNA Repair; Saccharomyces cerevisiae Proteins; Ubiquitin-Conjugating Enzymes; mutace; ubikvitin konjugující enzymy; Genes, Fungal; Alleles; adenin; Mutation; Ligases; ligasy; geny hub; oprava DNA